2015
DOI: 10.1002/2015gl063546
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of dimethylsulfide production by anoxic stress in natural seawater

Abstract: Dimethylsulfide (DMS) is produced by phytoplankton in the ocean and plays an important role in biogeochemical cycles and climate system of the Earth. Previous field studies reported a possible relationship between DMS enhancement and anoxic condition, although the governing processes are still to be identified. Here we show the first direct evidence for the enhancement of DMS production by natural planktonic assemblages caused by anoxic stress. Under the anoxic condition, DMS production was considerably enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These high concentrations could not be explained by any known pathways and may imply an unknown -most likely microbial -DMS production pathway under anoxic conditions either in the water column or in the underlying sediments (Shenoy et al, 2012). Only recently it was shown that phytoplankton communities exposed to anoxic conditions increase their DMS production significantly (Omori et al, 2015). This implies a potential accumulation of DMS at oxic-anoxic boundaries of coastal OMZs which, in turn, might result in high DMS emissions from shallow coastal zones during anoxic/sulfidic events.…”
Section: The Role Of Omzs In Trace Gas Emissionsmentioning
confidence: 99%
“…These high concentrations could not be explained by any known pathways and may imply an unknown -most likely microbial -DMS production pathway under anoxic conditions either in the water column or in the underlying sediments (Shenoy et al, 2012). Only recently it was shown that phytoplankton communities exposed to anoxic conditions increase their DMS production significantly (Omori et al, 2015). This implies a potential accumulation of DMS at oxic-anoxic boundaries of coastal OMZs which, in turn, might result in high DMS emissions from shallow coastal zones during anoxic/sulfidic events.…”
Section: The Role Of Omzs In Trace Gas Emissionsmentioning
confidence: 99%
“…Therefore, the oceanic DMS produced via multiple pathways can be affected by many biotic and abiotic factors, including temperature, salinity, solar radiation, mixed layer depth, nutrients, oxygen, acidity, etc. (Simó and Pedrós-Alió, 1999b;Vallina and Simó, 2007;Stefels, 2000;Zindler et al, 2014;Six et al, 2013;Omori et al, 2015;Stefels et al, 2007). In addition, seawater DMS has multiple removal pathways (bacterial consumption, photodegradation, sea-to-air ventilation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Wu et al (2018) reported that the DMS concentration declined in the hypoxic zone outside the Yangtze River and noted that the decreased phytoplankton biomass in the hypoxic zone was the main reason for the low DMS concentration. Omori et al (2015) used isotope labeling to culture natural planktonic assemblages under anoxic stress and reported that DMS production was considerably enhanced and DMS bacterial consumption was inhibited during a 1-hour laboratory culture. However, because the culture time was very short, this result does not re ect the changes in the microbial community related to the metabolism of dimethyl sulfur compounds or the potential ability to generate DMS over the long term.…”
Section: Introductionmentioning
confidence: 99%